A hybrid version of well-being: An attempt at operationalisation - Kwarciński, Tomasz; Ulman, Paweł (Journal of Public Governance, 2019)
Objectives: This paper aims to investigate the possibility of constructing a hybrid version of well-being and making an attempt at its operationalisation. Research Design & Methods: The theoretical framework is based on the capability approach of Amartya Sen and Martha Nussbaum, while the empirical part of the paper refers to a fuzzy set theory. Findings: We propose three measures of hybrid well-being, referring to (1) the minimum formula, (2) a mobility index, and (3) the concept of internalities. Implications / Recommendations: We are convinced that it is not only possible to create a philosophically informed measure of well-being, but also that this kind of measure can be crucial in the context of public policy due to its sensitivity to autonomy and adaptation problems. Contribution / Value Added: Findings of this research can be seen as an attempt to merge philosophical investigation with economics theories and applications.